2011
DOI: 10.1002/mrc.2747
|View full text |Cite
|
Sign up to set email alerts
|

Complete 13C NMR assignments for ent‐kaurane diterpenoids from Sideritis species

Abstract: In this work, the detailed NMR studies and full (13)C NMR assignments for five diterpenoids isolated from Sideritis caesarea and Sideritis athoa are described. The assignments are based on a combination of 1D and 2D NMR techniques including (1)H, (13)C, (1)H-(1)H COSY, gHSQC [(1)J(C,H)] and gHMBCδ(C) [(n)J(C,H)(n=2 and 3)] and NOESY experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
(21 reference statements)
1
17
0
Order By: Relevance
“…12,13 In a former study we reported 5 diterpenoids, all with the ent-kaurane skeleton, from the acetone extract of Sideritis caesarea. 11 The present study is the first report on the isolation and structure elucidation of its * Correspondence: halfonbe@boun.edu.tr flavonoid constituents. Although the flavone apigenin (2) and glycosylated flavonoids (3)(4)(5)(6)(7)(8) have been isolated from other Sideritis species, the trimethoxylated flavone penduletin (5,4'-dihydroxy-3,6,7-trimethoxyflavone)…”
Section: Introductionmentioning
confidence: 84%
“…12,13 In a former study we reported 5 diterpenoids, all with the ent-kaurane skeleton, from the acetone extract of Sideritis caesarea. 11 The present study is the first report on the isolation and structure elucidation of its * Correspondence: halfonbe@boun.edu.tr flavonoid constituents. Although the flavone apigenin (2) and glycosylated flavonoids (3)(4)(5)(6)(7)(8) have been isolated from other Sideritis species, the trimethoxylated flavone penduletin (5,4'-dihydroxy-3,6,7-trimethoxyflavone)…”
Section: Introductionmentioning
confidence: 84%
“…Most of the chemical studies on Turkish Sideritis species, particularly for diterpenic structures have been carried out by Topcu's group including Sideritis athoa [22], S. argyrea [23], S. dichotoma [24], S. sipylea [24], S. trojana [25], S. leptoclada [26], S. stricta [27], S. tmolea [28], S. condensata [29], S. arguta [30], S. congesta [31], S. niveotomentosa [32], S. brevibracteata [33], and several other Sideritis species [34]. Antioxidant and anticholinesterase activities of ent-kaurane diterpenoids from Sideritis arguta and S. congesta were studied by Topcu group, and 7-epi-candicandiol and sideroxol showed the highest butyrylcholinesterase inhibitory activity among the screened compounds, including the standard compound galanthamine [30,31,33,35].…”
Section: Introductionmentioning
confidence: 99%
“…The relative configuration of 3 was confirmed by saponification (K 2 CO 3 /MeOH). The 1 H NMR spectrum of the resulting diol compound was compared with the published spectrum of ent-3β-7α-dihydroxykaur-16-ene [15], and a perfect match was obtained, thus confirming the relative configuration of compound 3. According to the sign of the CE on ECD spectrum, the same absolute configuration was attributed to compound 3.…”
Section: Resultsmentioning
confidence: 62%
“…After extraction by ethylacetate, drying over anhydrous sodium sulfate, concentration under vacuum, and HPLC purification (heptane/ethylacetate, 1:1, v/v), the known compound ent-3β-7α-dihydroxykaur-16-ene (0.46 mg, 100%) was obtained. The spectral data of synthetic ent-3β-7α-dihydroxykaur-16-ene were identical to those of the natural compound [15].…”
Section: Saponification Of Compoundmentioning
confidence: 62%
See 1 more Smart Citation